KURSI TUNGGU MULTIFUNGSI - Nurul Hakim; Muhammad Choiru Zulfa (SULUH: Jurnal Seni Desain Budaya, 2020)
The waiting chair is an important tool and is used in public places in a room. The function of the waiting chair itself is for a place to wait. especially during waiting activities. In general, everyone likes the many functions and purposes that can be obtained in one item or product at a time. Apart from providing many advantages and also the ease with which multi-functional products can be used for various purposes, of course this is something extraordinary. combining various functions and purposes in one piece of furniture can save space while increasing the level of comfort. Based on this, the problems raised in this case are (1) How to make a multifunctional waiting chair design with burlap as an upholstery application, (2) What is the form of a multifunctional design in a waiting chair design to make it comfortable to use, (3) How to add value to the design waiting chair with burlap application.